PERAN KEWIRAUSAHAAN DALAM MEMBENTUK KARAKTER KEMANDIRIAN EKONOMI SANTRI - Habibulloh Habibulloh; Afria Rachmawati; Muhammad Subari (NATUJA: Jurnal Ekonomi Syariah, 2024)
Entrepreneurship in shaping the character of students' economic independence is very important. This research uses a qualitative descriptive method with a phenomenological approach. In data collection procedures, observation, interviews and documentation methods are used. Meanwhile, technical data analysis uses qualitative data analysis (data reduction, data presentation and conclusion drawing) From the results of research in the field it was found that entrepreneurial students at the Raudlatut Thalabah Setail Islamic boarding school played an important role in establishing economic independence. So with entrepreneurship students can live economically independently, this is proven by students being able to meet their own needs such as eating, being able to pay Islamic boarding school sharia and even being able to save even though it is only five thousand rupiahs per day. There are supporting factors for the entrepreneurship of Raudlatut Thalabah Setail students, namely commitment, being serious, oriented to be superior and carried out continuously or istiqomah. Then for the inhibiting factors for the entrepreneurship of Raudlatut Thalabah Setail students, namely incompetence, lack of expertise in controlling finances, location that is less strategic and less serious in running their business.